Analytical model for electromagnetic induction in pulsating ferrofluid pipe flows. (August 2021) - Wang, H.; Monroe, J.G.; Kumari, S.; Leontsev, S.O.; Vasquez, E.S.; Thompson, S.M.; Berg, M.J.; Walters, D.K.; Walters, K.B.
Highlights: Ferrofluidic induction is the generation of voltage via ferrofluid pulsation through a solenoid. Developed analytical model predicts energy harvesting capacity for pulsating ferrofluid. Model validated with experimental data vs pumping frequency and magnetic flux density. Induced EMF increases with higher pulse frequency and reduced magnet-solenoid spacing. Magnetic fluid-induced energy harvesting systems can be evaluated using the model presented. Abstract: Energy harvesting processes using ferrofluidic induction—a process that generates voltage via the pulsation of a ferrofluid (iron-based nanofluid) through a solenoid—have received increasing attention over the past decade. In this paper an analytical model is proposed to predict the induced electromotive force (EMF) based on the flow behavior and magnetic properties of a pulsating ferrofluid energy harvesting device. The ferrofluid is treated as an idealized series of discrete magnetic 'slugs' within passing through the solenoid, and the model identifies key parameters for describing and optimizing ferrofluidic induction in pulsating pipe flows. The resulting expression for induced EMF as a function of slug position relative to the solenoid is numerically integrated to determine the root mean square (RMS) of EMF during one pulsation cycle. Data from a previously documented study using an experimental induced EMF test rig is analyzed to find corresponding measured values of EMF RMS and used to validate the analytical model. Experimental and analytical results both show an increase in induced EMF with higher pulse frequency, increased number of bias magnets, and reduced spacing between the magnet and solenoid. At low magnetic flux densities and pumping frequencies, the EMF is negligible; with 0.3 mT magnetic flux density and 9 and 18 Hz pumping frequencies the measured RMS is nominally zero. For a 9 Hz pumping frequency the RMS value of the induced EMF is less than 1 μV at all magnetic flux densities. For the highest pumping frequency examined, 30 Hz, the induced EMF RMS is greater than 1 μV for all magnetic flux densities greater than 0.7 mT. As the experimentally measured values of EMF lie within the uncertainty bounds of the model, induced EMF can be predicted within an order of magnitude for magnetic fluid-induced energy harvesting systems.